Neo-deterministic seismic hazard maps of Kosovo - Brandmayr, Enrico; Vaccari, Franco; Romanelli, Fabio; Vlahovic, Gordana; Panza, G. F. (Vietnam Journal of Earth Sciences, 2021)
Kosovo is one of the most seismically active regions in Europe, lying within the Alpine-Mediterranean tectonic belt. Historical records for the region show several catastrophic earthquakes with epicentral intensity IX (MCS). However, due to Kosovo’s high population density, high prevalence of traditional construction, and insufficient enforcement of building codes, Kosovo is vulnerable to earthquake damage. In this study, we present earthquake hazard maps for bedrock conditions in Kosovo based on the well-known Neo-deterministic Seismic Hazard Assessment (NDSHA) method. NDSHA relies upon the fundamental physics of wave generation and propagation in complex geologic structures to generate realistic time series, used as input for the computation of several ground motion parameters, integrating the available knowledge of seismic history, seismogenic zones and morphostructural nodes. In accordance with continuum mechanics, the tensor nature of earthquake ground motion is preserved, producing realistic signals using structural models obtained by tomographic inversion and earthquake source information readily available in literature. Our maps are generally consistent with the observed intensity IX (MCS) and suggest that, in some instances, intensity X could be reached.